Think safe electricity (Home safety series, 1994)
This programme discusses safety outdoors around power lines, while kite flying, trimming trees, and during an electrical storm. Also includes hazards connected with space heaters, extension cords, frayed cords, breaker boxes, and using small appliances (curling irons, etc.) around water and how to eliminate the hazards. Dramatizes incident involving a man being electrocuted from overtaxing an outlet.